Lokalizacja firm źródłem przewagi konkurencyjnej. Koncepcje rozwoju gospodarki w oparciu o skupiska małych i średnich firm - Figuła, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2008)
The author presents concepts of development of industrial clusters facilitating development and mutual reinforcement of small and medium enterprises. Each subject affected by market forces experiences the significance of location and the resulting consequences. Alfred Marshall was the first to observe the significance of location and emerging industrial districts supported by social and economic forces. A. Hirschmann, G. Myrdal and F. Perroux pioneered the idea of external and internal factors, historical events and theories of polar growth. M.E. Porter observed that location and the surrounding cluster constitutes a source of advantage in competition. Nobel Prize winner in economics, Paul Krugman, points out that industrial district constitute self-propelling mechanisms due to their favourable location.
Keywords: małe i średnie przedsiębiorstwa; konkurencyjność; rozwój gospodarczy; wzrost gospodarczy